(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
Issues related to accessibility are increasingly in vogue in the information society, the research had the general objective of studying the accessibility strategies adopted by the Innovation Center of the Technological Pole of Jaraguá that seek to promote equal opportunities for People with Disabilities and strengthen diversity in the technology and innovation scenario in the State of Alagoas. The research methodology is applied, quantitative-qualitative. The project is underway by the Postgraduate Program in Information Science at the Federal University of Alagoas, still in its initial phase, with partial results when identifying companies and institutions located in the Technological Hub.